2017
DOI: 10.3892/ol.2017.6052
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of miR-21 induces SK-N-SH cell apoptosis and inhibits proliferation via PTEN/PDCD4

Abstract: MicroRNA (miR/miRNA)-21 is a well-known oncogenic miRNA that is overexpressed in various types of tumors. The tumor-suppressor genes programmed cell death 4 (PDCD4) and phosphatase tensin homologue (PTEN), are targets of miR-21, and are underexpressed in several types of cancer. However, the expression of miR-21 and its target genes in neuroblastoma (NB) remains unclear. In the present study, a miR-21 inhibitor oligonucleotide was transfected into the SK-N-SH cell line, and the expression of miR-21, PTEN and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Usually one miRNA targets multiple genes. As PDCD4 has been frequently reported as a target of miR-21-5p, the role of miR-21-5p in PDCD4 expression in TSCC requires additional study (21). In the present study, the luciferase reporter assay revealed that PDCD4-UTR-pMIR (WT) was significantly increased by miR-21-5p inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually one miRNA targets multiple genes. As PDCD4 has been frequently reported as a target of miR-21-5p, the role of miR-21-5p in PDCD4 expression in TSCC requires additional study (21). In the present study, the luciferase reporter assay revealed that PDCD4-UTR-pMIR (WT) was significantly increased by miR-21-5p inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT pathway is closely associated with apoptosis. This pathway controls cell proliferation, growth, translation, migration and survival, and overactivation of this signaling pathway is associated with poor prognosis (21,22). Activated PI3K may activate downstream protein kinase AKT; Activated AKT is able to phosphorylate Bax, inactivate Bax and inhibit Bax and Bcl-2 to form dimers, thereby resulting in Bcl-2 dissociation and an anti-apoptotic effect (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Eight of 10 upregulated circRNAs and two of five downregulated circRNAs were finally verified in 20 paired samples ( Figure 2 A and B ). Our previous study had shown that miR-21 plays a significant role in the regulation of proliferation and apoptosis in NB, 6 , 17 so we selected another seven circRNAs for analysis, whose predicted target miRNA was miR-21. Real-time qRT-PCR confirmed that three miR-21-related circRNAs, including circRNA-TBC1D4 (average FoldChange = 18.7; P = 0.0002), circRNA-NAALAD2 (average FoldChange = 5.6; P = 0.0032) and circRNA-TGFBR3 (average FoldChange = 23.3; P = 0.0079), were significantly downregulated in NB samples ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study focused on the oncogenic gene miR-21 in NB and found that miR-21 may regulate the potential targets PTEN/PDCD4 to promote apoptosis. 6 , 17 In addition, miR-21 functions as a significant common carcinogen in a variety of cancers, such as gliomas, 23 colon cancer, 24 cutaneous malignant melanoma 25 and retinoblastoma. 26 Three miR-21-related circRNAs, circRNA-TBC1D4, circRNA-NAALAD2 and circRNA-TGFBR3, were confirmed to be overexpressed in adjacent adrenal tissue compared to tumor tissue and this was verified by qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of miR-96 may suppress programmed cell death protein 4 (PDCD4) and subsequently decrease apoptosis. It is known that reduction of miR-21 promotes apoptosis by inhibiting the expression of phosphatase and tensin homolog (PTEN) and PDCD4 [ 38 ] . Down regulation of the pro-apoptotic factors PTEN and PDCD4 can increase expression of the cell survival factor Akt or protein kinase B, leading to a reduction in apoptosis in SCI.…”
Section: Potential Roles Of Mirnas In Scimentioning
confidence: 99%